2011
DOI: 10.1021/bi2002086
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular Crowding Extended to a Heptameric System: The Co-chaperonin Protein 10

Abstract: Experiments on monomeric proteins have shown that macromolecular crowding can stabilize toward heat perturbation and also modulate native-state structure. To assess the effects of macromolecular crowding on unfolding of an oligomeric protein, we here tested the effects of the synthetic crowding agent Ficoll 70 on human cpn10 (GroES in E. coli), a heptameric protein consisting of seven identical β-barrel subunits assembling into a ring. Using far-UV circular dichroism (CD), tyrosine fluorescence, nuclear magnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 87 publications
3
18
0
Order By: Relevance
“…It follows that an experiment designed to follow the concerted formation of a large oligomer would be expected to be much more sensitive to excluded volume effects than one designed to follow the formation of a homo- or heterodimer. Large changes in self-association equilibria were indeed observed in studies of the effect of crowding on the concerted formation of hexamers of ClpB 34 , heptamers of cp10 32 and decamers of bovine pancreatic trypsin inhibitor 86 .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 78%
“…It follows that an experiment designed to follow the concerted formation of a large oligomer would be expected to be much more sensitive to excluded volume effects than one designed to follow the formation of a homo- or heterodimer. Large changes in self-association equilibria were indeed observed in studies of the effect of crowding on the concerted formation of hexamers of ClpB 34 , heptamers of cp10 32 and decamers of bovine pancreatic trypsin inhibitor 86 .…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 78%
“…While this increase in stability presumably arises due to the same electrostatically and sterically driven excluded volume effects postulated to underlie solution-phase crowding, 17 its magnitude is rather greater than the effects typically seen in solution. 18,28 This difference may arise in part due the high local concentrations of DNA that can be achieved in the surface-bound state, which approach 100 mg/mL within one contour length (the 15 nm length of the unfolded DNA chain) of the surface. This said, the stability of proteins (in the dilute regime) typically increases by only ∼1 kJ/mol with the addition of ∼100 mg/mL of highly soluble, nonbiomolecular crowding agents, such as polyvinylpyrrolidone 29 or dextran, 30,31 suggesting that additional mechanisms may be playing a role in our results.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, stabilization much greater than that for binary complexes of single‐domain proteins is observed. For example, using magnetic relaxation dispersion, Snoussi and Halle [76] found a 17000‐fold increase in the association constant for BPTI decamer by 230 g/l of dextran 10 K. Similarly, Aguilar et al [77], based on tryptophan fluorescence, found that 300 g/l Ficoll resulted in a 300‐fold increase in the association constant for heptamer formation of mitochondrial cochaperonin protein 10.…”
Section: Binding Oligomerization and Aggregationmentioning
confidence: 98%